Reconhecimento e uso de testes experimentais no laboratório escolar - Alessandro Damasio Trani Gomes (2005)
The use of investigative activities in science teaching has been extensively discussed. However, their use as a teaching-learning strategy depends, mainly, on the students abilities of planning and conducting those investigative activities in order to discuss the data gathered. Among such abilities, we may highlight the one of realising adequate and consistent empirical tests, i.e. the ability to conduct experiments in which only the focused variable, whose effect should be determined, is changed, whilst all the other variables are kept constant so that the experimenter can infer causal relationships between all the involved aspects. In this research, we tried to characterise both the knowledge and the strategies that students use to conduct investigative activities involving computational simulations. Our initial hypothesis was that the knowledge each individual use during the whole activity can be characterized according to four aspects: (a) the aim s/he attributes to the task realised; (b) the partial results obtained during the activity; (c) the domain-specific knowledge related to the activity; (d) the causality relationship between the variables. The main focus of our analysis was the investigation of the recognition of adequate and consistent empirical tests, followed by their use to obtain valid data to solve a practical problem. We believe the methodology we developed both had made possible to view the investigative activities conducted by the students as a whole and had bridged a gap previously identified in the literature, i.e. the lack of a more comprehensive analysis of empirical activities that include, if not all, the main aspects of scientific reasoning. 186 students from the first year of the medium level of a federal public school participated in the study. The results show that part of these students, even attending lab classes weekly, still have many difficulties in recognising and using an efficient variable control, in using data to generate useful conclusions and in both recognising and following the aims of the activities. From such data, as well as other results, we discuss educational implications from this research to science teaching. We also point out some new perspectives for research in this area.